Cutaneous nociception and neurogenic inflammation evoked by PACAP38 and VIP - Schytz, Henrik Winther (Springer Milan, 2010)
Pituitary adenylate cyclase-activating peptide-38 (PACAP38) and vasoactive intestinal peptide (VIP) belong to the same secretin–glucagon superfamily and are present in nerve fibers in dura and skin. Using a model of acute cutaneous pain we explored differences in pain perception and vasomotor responses between PACAP38 and VIP in 16 healthy volunteers in a double-blind, placebo-controlled, crossover study. All participants received intradermal injections of 200 pmol PACAP38, 200 pmol VIP and placebo into the volar forearm. Measurements included pain intensity on a visual analog scale (VAS), blood flow by laser Doppler flowmetry, visual flare and wheal. Pain intensities after PACAP38 and VIP were mild and limited to a short time of about 100 s after injection. The area under the VAS-time curve was larger following PACAP38 (P = 0.004) and VIP (P = 0.01) compared to placebo. We found no statistical difference in pain perception between PACAP38 and VIP. Skin blood flow increase, flare and wheal were larger after both PACAP38 (P = 0.011) and VIP (P = 0.001) compared to placebo. VIP induced a considerably larger increase in skin blood flow, flare and wheal than PACAP38 (P = 0.002). In conclusion, we found that peripheral nociceptive cutaneous responses elicited by PACAP38 and VIP are similar in healthy volunteers. This suggests that acute pain and vasomotor responses following intradermal injections of PACAP38 and VIP are primarily mediated by VPAC receptors.